The Level of Basic Thinking Skills to Fourth-Grade Pupils in Science Subject/ A field Study at the basic Education Schools (first circle) in Jableh City - زمرد, أميرة; يوسف, سمر; عيسى, مدار (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This Research aimed to assist the level of Basic Thinking Skills: Remembering, Observing, Representing, Comparing, Classification, Ordering, Explaining, Identifying Attributes and Components, Identifying Relationships and Patterns, Identifying Errors, Induction, Deduction, Elaborating and Establishing Criteria, in Science to Fourth-Grade Students, and investigate differences in the level of basic thinking skills according to gender. For that, the descriptive method was used, and the search tool was a test of basic thinking skills in science subject, which was prepared by the researcher. And the characteristics of psychometric were studied. The Final test consists of (70) items, divided evenly into (14) skills. The simple random sample consisted of (225) fourth grade students in Jableh city. The results showed that the level of basic Thinking Skills to fourth grade in science subject was average .And the level of representing, explaining, identifying attributes and Components, identifying Relationships and Patterns, identifying Errors, induction, deduction, elaborating and establishing criteria skills was low, while the level of Remembering, Observing, Comparing, Classification and Ordering skills was average. and there were no significant differences among females and male’s scores on test of basic thinking skills. Also, females possess comparing and representing skills are better than males, but males possess deduction are better females.